Unpacking the extractivist state: The role of weak state agencies in promoting institutional change in Peru. Issue 1 (January 2019) - Gustafsson, Maria-Therese; Scurrah, Martin
Highlights: There is a tendency in the literature on resource-rich states to focus on either political and economic elites, or local communities. This article seeks to unpack the extractivist state and shifts the focus to the role of entrepreneurial actors within the state to promote institutions for inclusive and sustainable development. A new framework, focused on the strategic ability of entrepreneurial agencies, is developed to explain more or less successful attempts of institutional strengthening. An analysis of the Peruvian ministry's efforts to institutionalize participatory zoning and related planning processes (2008–2016) is conducted. Abstract: When a resource boom has begun it is often challenging to develop institutions for governing natural resources in an inclusive and sustainable manner. Whereas existing studies on resource-rich states have focused on political elites or social mobilization for explaining attempts to strengthen such institutions, we know less about the role of less influential reform-oriented agencies (e.g. environmental agencies, subnational governments), and what explains how and why on rare occasions they are surprisingly effective in driving institutional change. Theoretically, we draw on theories on institutional weakness and change. Based on 139 interviews, we analyze the outcomes of different strategies adopted by the Peruvian Environmental Ministry (MINAM) to enforce a participatory zoning and land-use planning (LUP) reform between 2008 and 2016. We argue that weak agencies are dependent upon strategic ability, here referring to the skill of an agency to adapt its strategies to reigning political opportunities, thereby contributing to defending or expanding its autonomy vis-á-vis powerful groups and building alliances with societal actors that could defend it from opponents. By unpacking the dynamics within a resource-rich state, we contribute with a nuanced analysis of the challenges of building and effectively enforcing institutions in a context of expanding extractive industries.